2009
DOI: 10.1097/bcr.0b013e3181b485d3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Virtual Reality on Pain and Range of Motion in Adults With Burn Injuries

Abstract: Few studies have empirically investigated the effects of immersive virtual reality (VR) on postburn physical therapy pain control and range of motion (ROM). We performed a prospective, randomized controlled study of the effects of adding VR to standard therapy in adults receiving active-assisted ROM physical therapy, by assessing pain scores and maximal joint ROM immediately before and after therapy on two consecutive days. Thirty-nine inpatients, aged 21 to 57 years (mean 35 years), with a mean TBSA burn of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(136 citation statements)
references
References 16 publications
6
124
0
6
Order By: Relevance
“…Advance Ice-features Distraction: Several studies that go beyond the line of single distraction strategy incorporated ice-features in the Virtual Environment (VE) (e.g., Icy 3D Canyon, SnowWorld) [17,18,19], [38,39]. As a result, VR with Snow-VE creates an illusion of a "cooling" effect by looking at the snowy environment.…”
Section: Future Research and Conclusionmentioning
confidence: 99%
“…Advance Ice-features Distraction: Several studies that go beyond the line of single distraction strategy incorporated ice-features in the Virtual Environment (VE) (e.g., Icy 3D Canyon, SnowWorld) [17,18,19], [38,39]. As a result, VR with Snow-VE creates an illusion of a "cooling" effect by looking at the snowy environment.…”
Section: Future Research and Conclusionmentioning
confidence: 99%
“…Furthermore, there is now a growing evidence base to support their use in a variety of different rehabilitation applications including mobility and aerobic fitness [13][14][15], post-stroke rehabilitation of hand-arm function [16][17][18], balance [14,[19][20][21], pain distraction while undergoing treatment/therapy [22], and treatment of amblyopia ("lazy eye") [23].…”
Section: Introductionmentioning
confidence: 99%
“…Hoffman et al first reported that VR could alleviate pain perception during painful burn care in adolescent patients [6]. The application of VR for pain control during burn care has been the most intensively studied application [7][8]. Other procedures to which VR has been applied include dental procedures [9] and intravenous placement [10].…”
Section: Virtual Reality and Pain Managementmentioning
confidence: 99%